2007
DOI: 10.1175/jcli4142.1
|View full text |Cite
|
Sign up to set email alerts
|

Decadal Variability of the Kuroshio Extension: Observations and an Eddy-Resolving Model Hindcast*

Abstract: Low-frequency variability of the Kuroshio Extension (KE) is studied using observations and a multidecadal hindcast by a high-resolution (0.1°), eddy-resolving, global ocean general circulation model for the Earth Simulator (OFES). In both the OFES hindcast and satellite altimeter observations, low-frequency sea surface height (SSH) variability in the North Pacific is high near the KE front. An empirical orthogonal function (EOF) analysis indicates that much of the SSH variability in the western North Pacific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
232
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 260 publications
(249 citation statements)
references
References 46 publications
14
232
2
1
Order By: Relevance
“…In this study, we consider the KE jet as a single jet, following previous studies (e.g., Qiu and Chen 2005;Taguchi et al 2007;Sasaki and Schneider 2011). Thus, we ignore the bifurcation branches of the KE jet (e.g., one branch around the Shatsky Rise shown in Mizuno and White 1983), and only focus on ring formation and absorption by the main part of the KE jet.…”
Section: B a Methods To Detect A Ring Formationmentioning
confidence: 99%
“…In this study, we consider the KE jet as a single jet, following previous studies (e.g., Qiu and Chen 2005;Taguchi et al 2007;Sasaki and Schneider 2011). Thus, we ignore the bifurcation branches of the KE jet (e.g., one branch around the Shatsky Rise shown in Mizuno and White 1983), and only focus on ring formation and absorption by the main part of the KE jet.…”
Section: B a Methods To Detect A Ring Formationmentioning
confidence: 99%
“…It is well known that the KE jet undergoes prominent fluctuations on decadal timescales (e.g., Deser et al 1999;Schneider et al 2002;Taguchi et al 2007;Sasaki and Schneider 2011;Sasaki et al 2013). Qiu and Chen (2005b) showed that when the eddy activity in the KE region is high and low, the KE jet is weakening and strengthening, respectively, and referred to the former as a stable state and the latter as an unstable state.…”
Section: Introductionmentioning
confidence: 99%
“…In reality, however, oceanic Rossby waves forced by wind stress variations in the central Pacific propagate westward, while associated sea surface height anomalies become concentrated into the jet to effectively modify it (Sasaki and Schneider 2011). The wind variations thus act as a "pace maker" for the quasi-decadal KE variability by triggering its regime transition (Taguchi et al 2007). Meanwhile, modulated mesoscale eddy activity can lead to modulations in sub-mesoscale streamers and associated vertical motion (Sasaki et al 2014).…”
mentioning
confidence: 99%